(untitled) (Texas Journal of Multidisciplinary Studies, 2024)
Digital currencies, including cryptocurrencies and central bank digital currencies (CBDCs), are rapidly reshaping the global financial ecosystem. While they offer unparalleled advantages, such as financial inclusion, enhanced transaction speed, and decentralization, these technologies also pose significant ethical challenges. Issues such as privacy concerns, environmental sustainability, financial inequality, and regulatory dilemmas highlight the complex ethical landscape of digital currencies. This article examines the interplay between digital currencies and ethics, delving into their socio-economic impacts, potential risks, and strategies for addressing these challenges. Drawing on case studies and expert insights, this article emphasizes the importance of developing ethical frameworks to ensure digital currencies contribute positively to global economic development and social equity.